2016
DOI: 10.4314/star.v4i4.5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varieties and Population of Intercropped Soybean with Maize on Yield and Yield components at Haro Sabu, Western Ethiopia

Abstract: The field experiment was carried out at Haro Sabu Agriculture Research Center, during 2013 with the objectives of determining the effect of varieties and population densities of soybean intercropped with maize on yield and yield components of associated cr productivity of the system. The experiment was laid out in RCBD with three replication in factorial combination of three soybean varieties (Boshe, Ethio and three soybean plant populations (25%, 50% and 75%) along with respec crop of soybean varieties and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
2
9
0
Order By: Relevance
“…Also agreed with the results of this study, Rezaei-Chianeh et al [32] showed reduction in the yield of faba bean under intercropping system. This experimental result is supported by Teshome et al [34] revealed that the maximum grain yield was obtained from sole cropping of soybean than intercropping in maizesoybean intercropping. Mean grain yield of common bean in the intercrop systems was significantly lower than the sole crop yield of common bean.…”
Section: Treatmentssupporting
confidence: 71%
See 1 more Smart Citation
“…Also agreed with the results of this study, Rezaei-Chianeh et al [32] showed reduction in the yield of faba bean under intercropping system. This experimental result is supported by Teshome et al [34] revealed that the maximum grain yield was obtained from sole cropping of soybean than intercropping in maizesoybean intercropping. Mean grain yield of common bean in the intercrop systems was significantly lower than the sole crop yield of common bean.…”
Section: Treatmentssupporting
confidence: 71%
“…Maize (Zea mays L.) and common bean (Phaseolus vulgaris L.) are important food and cash crops cultivated for subsistence on smallholder farms in many parts of the world, including Sub-Saharan Africa. It is originated in Central America and was introduced to Ethiopia during the 1600s to 1700s [34]. In Ethiopia maize is one of the most important cereal crops grown in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Getachew(2007) also reported that higher harvest index was from intercropped maize with potato than sole cropped maize. In contrary to this, Gutu et al(2015) reported sole maize cropping system gave higher harvest index (0.39) than intercropped maize and soybean (0.37). Plant population: Different authors reported highest HIs obtained at high plant population densities.…”
Section: Environmental Variationmentioning
confidence: 61%
“…Kerby et al (1990) pointed out that high plant density in cotton resulted more dry matter leaves and stems relative to fruit and thereafter low harvest index (HI). The higher number of HI (38.11%) was obtained from 25% (83, 333 plants /ha) soybean population than 50% and 75% soy bean populations (Gutu et al, 2015). Nutrients: Application of potassium (K) at the highest rate (90 kg ha -1 ) increased Harvest index (0.39) due higher K level was attributed to the more dry matter partitioning into the reproductive parts (ears) of maize (Amanullah et al,2015).…”
Section: Environmental Variationmentioning
confidence: 99%
“…Characteristics, such as number of seeds per pod and 100 seed weight, are mostly influenced by genetic factors [38]. Similarly, Solomon et al [39]; and Teshome et al [40], reported that number of seeds per pod was significantly not different due to the main effects of soybean varieties, plant densities and cropping system. In contrast, Mohammed & Tessema [41], reported significant effect of varieties on number of seeds per pod of soybean varieties regardless of row spacing and interaction of variety and row spacing.…”
Section: Number Of Seeds Per Podmentioning
confidence: 99%